MODEL FOR FORMATION OF ARTISTIC CULTURE FUTURE ARTISTS-DESIGNERS - Semenyuk, Anton (Educological discourse, 2018)
The article is devoted to the study of the model of the formation of the artistic culture of future artists-designers in the process of vocational training. It has been determined that the artistic culture of future designers is a complex formation of the personality, which includes a set of artistic abilities in the artistic realm, conscious feelings, motives of artistic activity, readiness for the realization of creative potential through harmonious transformation of reality and the inner world for the productive exercise of educational and professional functions. The main scientific approaches to the formation of the artistic culture of future specialists (personal, competency, cultural, axiological, integral) are presented. The contents of the model of formation of the artistic culture of future designers are characterized and substantiated. The model of formation of the artistic culture of future designers includes: target, methodological, informative, active, productive blocks. The target unit reflects goals, tasks for the formation of the artistic culture of future designers. The methodological block of the model provides scientific approaches to the strategy of forming the artistic culture of future designers, as well as the principles of formation of the phenomenon under study. The content block of the model for the formation of the artistic culture of future designers reflects the content, structure of the artistic culture of future designers and methodology for the formation of the phenomenon under study. The activity block of the model of formation of the artistic culture of future artists-designers characterizes the pedagogical conditions of formation of the investigated phenomenon in the process of vocational training. The effective block of the model demonstrates the dynamics of the formation of the artistic culture of future designers by means of selected criteria (artistic awareness, motivational maturity, artistic sensuality, creative independence, designer competence), levels of formation and achieved changes in accordance with the intended purpose.